2019
DOI: 10.1128/aac.01213-19
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Mycobacterium tuberculosis to Biofilm Growth Is Genetically Linked to Drug Tolerance

Abstract: Mycobacterium tuberculosis spontaneously grows at the air-medium interface, forming pellicle biofilms, which harbor more drug-tolerant persisters than planktonic cultures. The underlying basis for increased persisters in M. tuberculosis biofilms is unknown. Using a transposon sequencing (Tn-seq) approach, we show here that multiple genes that are necessary for fitness of M. tuberculosis cells within biofilms, but not in planktonic cultures, are also implicated in tolerance of bacilli to a diverse set of stress… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 62 publications
4
57
0
Order By: Relevance
“…Mtb spontaneously grows at the air-liquid interface, forming pellicle biofilms with elevated drug-tolerant persisters compared to planktonic cultures. The intrinsic drug tolerance of biofilm cells was found to determine the frequency of persisters and isonitrile lipopeptide necessary for the architectural development of Mtb biofilms (Richards et al, 2019).…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…Mtb spontaneously grows at the air-liquid interface, forming pellicle biofilms with elevated drug-tolerant persisters compared to planktonic cultures. The intrinsic drug tolerance of biofilm cells was found to determine the frequency of persisters and isonitrile lipopeptide necessary for the architectural development of Mtb biofilms (Richards et al, 2019).…”
Section: Mycobacterium Tuberculosismentioning
confidence: 99%
“…The formation of biofilms contributes to stress survival, since these dense multicellular aggregates, in which cells are embedded in an extracellular matrix of self-produced polymers, represent a self-constructed protective 'niche' 21 that yet remains metabolically active even after reaching maturity 22 . In M. tuberculosis complex bacteria, biofilm production in vitro has been shown to harbor drug-tolerant bacteria 7 and to be genetically linked to this phenotype 8 . Drug-tolerant mycobacteria may comprise a fraction of the population, as mature M. tuberculosis biofilms showed sensitivity to antibiotic treatment when assessed with microcalorimetry (IMC) and tunable diode laser absorption spectroscopy 22 .…”
Section: Discussionmentioning
confidence: 99%
“…In M. tuberculosis complex bacteria, biofilm production in vitro has been shown to harbor drug-tolerant bacteria 7 and to be genetically linked to this phenotype 8 . Drug-tolerant mycobacteria may comprise a fraction of the population, as mature M. tuberculosis biofilms showed sensitivity to antibiotic treatment when assessed with microcalorimetry (IMC) and tunable diode laser absorption spectroscopy 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Tn-seq screening for M. tuberculosis mutants unable to form biofilms revealed that several genes required for biofilm formation were also involved in stress and drug tolerance. It is possible that the harsh environment found in the biofilm, characterized by nutrients and oxygen depletion and mechanical stresses, selects a bacterial population intrinsically tolerant to exogenous stresses, including drug exposure, therefore increasing the frequency of persisters ( Richards et al, 2019 ).…”
Section: Mycobacterial Biofilms a Role In Tolerance And Persistencementioning
confidence: 99%